Langkah Strategis Penyelesaian Pegawai Tenaga Honorer di Lingkungan Instansi Pemerintah Pusat dan Pemerintah Daerah - Asa, La Indo (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2023)
This study aims is to find out the Strategic Steps for Completion of Honorary Employees in the Environment of Central Government Agencies and Regional Governments in Central Buton Regency at the Office of the Ministry of Religion of Central Buton Regency, the formulation of the problem in this paper is; What are the Strategic Steps for Completion of Honorary Staff in Central Government Agencies and Regional Governments at the Office of the Ministry of Religion in Central Buton Regency? While this research uses qualitative research methods, the type of research used by researchers is descriptive. The research results show that; With the issuance of Circular No. b/185/m.sm.02.03/2022 regarding the elimination of honorarium, the government must respect the rights and obligations of the community and maintain their welfare. This also applies to the community, depending on the capacity of the honorarium they accommodate or receive. Thus, the mandate of the Government Regulation can provide status certainty for non-ASN employees to become ASN because ASN already has a standard of income/compensation. Meanwhile, by becoming an outsourced worker in a company, the wage system is subject to the Manpower Law, where there is a regional minimum wage/provincial minimum wage (UMR/UMP), especially in the Ministry of Religion. So that the Ministry of Religion can reconcile the employment status of non-ASN employees (non-PNS, non-PPPK, and ex-Honorary Staff).